2011
DOI: 10.1007/s00125-011-2175-8
|View full text |Cite
|
Sign up to set email alerts
|

Altered gap junctional communication and renal haemodynamics in Zucker fatty rat model of type 2 diabetes

Abstract: Aims/hypothesis We examined the link between altered gap junctional communication and renal haemodynamic abnormalities in diabetes in studies performed on Zucker lean (ZL) and the Zucker diabetic fatty (ZDF) rat model of type 2 diabetes. Methods The abundance of connexin (Cx) 37, 40 and 43 was assessed by western blot and immunohistochemistry. Renal haemodynamics was characterised with GAP peptides, which are Cx mimetics, to inhibit gap junctions as a probe in both strains. Results ZDF rats exhibited higher pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
33
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 51 publications
7
33
0
Order By: Relevance
“…Renal renin and angiotensinogen contents increase in diabetes [43]. Although plasma renin activity is similar in Zucker diabetic fatty and Zucker lean rats [13], preliminary data from the same group show elevated intrarenal ANG II content in Zucker diabetic fatty rats, which is appropriately reduced by high salt intake [44]. In 2K1C clipped kidney, the renin content shows an early massive rise, but later decreases to control levels, while that of the non-clipped kidney becomes vanishingly small [45].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Renal renin and angiotensinogen contents increase in diabetes [43]. Although plasma renin activity is similar in Zucker diabetic fatty and Zucker lean rats [13], preliminary data from the same group show elevated intrarenal ANG II content in Zucker diabetic fatty rats, which is appropriately reduced by high salt intake [44]. In 2K1C clipped kidney, the renin content shows an early massive rise, but later decreases to control levels, while that of the non-clipped kidney becomes vanishingly small [45].…”
Section: Discussionmentioning
confidence: 94%
“…Reduced efficiency of autoregulation increases susceptibility to, and rate of progression of, hypertensive nephropathy [9][10][11]. It is often considered that autoregulation is impaired in diabetes, and diabetic hyperfiltration has been attributed to enhanced transmission of systemic pressure to glomeruli [2,12,13]. However, efficient autoregulation has also been reported in diabetes [7,[14][15][16], and the literature has been described as contradictory [14,17].…”
Section: Introductionmentioning
confidence: 99%
“…Reduced cell adhesion, cell coupling and cell-to-cell communication have profound effects on overall integrity and function of the proximal tubule, and altered GJIC and renal haemodynamics have recently been reported in a Zucker fatty rat model of type2 diabetes [49]. In the current study, we concede that our in vitro data provide a minimalistic model of the early events in EMT and thus recommend caution in translating these novel findings to the in vivo situation, where the multifactorial molecular pathology of renal fibrosis may modify responses.…”
Section: Discussionmentioning
confidence: 99%
“…Kuroki et al (15) demonstrated that high glucose enhanced phosphorylation of Cxs, impairing gap junction functions (15). Using ZDF rats lacking leptin receptors (45), we have shown that reduced expression and enhanced phosphorylation of Cxs in the JGA relate to suppressing TGF signal transduction, resulting in almost complete abolition of renal autoregulation (32). Previous data indicated that P 2 receptor inhibition resulted in partial attenuation of autoregulation, including TGF (30).…”
mentioning
confidence: 90%